중⋅저층 건축물 소방시설 설계⋅준공도서 비교를 통한 공사비 및 설비별 설치비율 분석에 관한 연구 - 엄진형(Jin-Hyeong Eom); 이윤하(Yoon-Ha Lee); 최준호(Jun-Ho Choi) (한국화재소방학회 논문지, 35(2), 2021)
건축설계안의 변경 등으로 인해 소방시설 공사과정에서 최초 소방시설 설계안이 변경될 수도 있다. 이러한 ‘건축허가등의 동의단계에서의 설계도서’(이하 설계도서)와 ‘사용승인 동의단계에서의 설계도서’(이하 준공도서)의 차이는 결국 공사금액과 소방시설의 성능차로 이어질 수 있다. 따라서 건축물의 화재안전성 확보와 인명 피해 방지를위해 관련 사례분석과 그에 따른 제도적 보완이 필요하다. 본 연구에서는 최근 완공된 6개 건축물을 대상으로 최초설계안의 소방시설별 현장 적용비율을 분석하고, 제도적 보완 필요성을 제언하였다. 그 결과, 설계변경으로 인해 공사비와 순공사비는 원설계안에 비해 최대 19% 정도를 절감할 수 있었다. 특히 스프링클러설비는 준공도면에서 최초설계도면 대비 78.7%만 일치한 것으로 나타나 소방시설 가운데 설계변경 비율이 가장 컸다. The initial fire-fighting facility design plan may need to be changed during the construction of fire-fighting facilitiesbecause of alterations in the architectural design or the flexibility of the site situation. The difference between the 'designdrawings at the stage of consenting for building approval' (Original design drawings) and the 'design drawings at the stageof consenting for use approval' (Completion drawings) ultimately leads to changes in the construction cost and in theperformance of the fire-fighting facility. Therefore, to secure the fire safety of buildings and prevent human casualties,relevant case analyses and consequent institutional and systematic supplementation are necessary. In this study, six recentlycompleted buildings were selected as target sites, the application rate of each fire-fighting facility in the initial design wasanalysed, and the need for institutional supplementation was suggested. As a result, owing to the design change, theconstruction cost and net construction cost could be reduced by up to 19% compared to those based on the original design. In particular, In particular, the sprinkler facility was found to match only 78.7% of the original design drawing in thecompletion drawing, showing the largest rate of design change among fire-fighting facilities. KCI Citation Count: 0